Characteristics and Experiences of Nurse Mentors Towards Nursing Clinical Mentorship: : A Case of Meru County - Kaimuri, MaryJoy; Mutea, Prof Naomi; Karani, Caroline (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Clinical mentorship education enhances learning, retention, acquisition of skills and clinical competencies of nursing students. Clinical mentorship programs play a critical role for clinical education of nursing students. Shortage of nurses in Kenya hinders optimal healthcare services and student mentorship. The nurse-patient ratio is 8.3: 10,000 population compared to 25: 10,000 WHO recommendations. The Nursing Council of Kenya (NCK) requires that one instructor mentors ten students. Kenya has committed to increasing the healthcare workforce leading to the growth of nursing schools and student enrollment, yet, formalised nursing mentorship is lacking. Qualified nurses in hospitals are expected to play a dual role of serving their employer and mentorship/preceptorship of students, yet the university does not compensate them sufficiently. Most universities utilize government and faith-based hospitals for training, meaning that they do not own the hospitals. The nursing school has no control on what and how clinical mentorship is done. Currently, there are no national or NCK guidelines and standards on mentor qualifications, though they play a major role in nursing education. It is also unclear how qualified nurses who act as mentors experience the clinical mentoring of student nurses in resource-limited settings. This study evaluated the characteristics and experiences of nurse mentors in selected health facilities in Meru County. Baseline data was collected using a structured questionnaire. Qualitative content analysis was utilized to develop themes and categories emerging from the data. Baseline survey results indicate that 53.5% (n=38) of the nurse mentors had a diploma in nursing qualification with 28.2% (n=20) having worked as nurses for 11-15 years. The majority [78.9% (n=56)] of the nurses had mentored students for 1-5 years in the current unit/ward. However, 59.2% (n=42) of the nurses rated their experience mentoring students as neutral. Most [69.0% (n=49)] of the nurse mentors indicated that there are no guidelines/policies in the hospitals to guide the mentorship process, with 95.8% (n=68) stating that there is a need for clinical mentorship training. The majority of the nurse mentors [32.4% (n=23)] stated that their motivation to mentor is a result of moral duty, job responsibility, and competency improvement. The study concluded that nurses are generally motivated to mentor student nurses and there is an urgent need for formal training of clinical nurse mentors in order to improve clinical teaching and learning.